TEKNOLOGI DALAM PENGEMBANGAN SDM - Muhammad Mursal Rafsanjani; Khairul Rizki; Machdum Bachtiar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the role of technology in Human Resource Development (HRD) in the digital era. The research method used is library research by reviewing various academic sources such as books, journals, and relevant scholarly articles. The findings indicate that the implementation of technologies such as Learning Management Systems (LMS), e-learning, microlearning, Virtual Reality (VR), Augmented Reality (AR), and Artificial Intelligence (AI) significantly enhances the effectiveness and efficiency of training processes. Technology enables learning to become more flexible, adaptive, interactive, and data-driven, thereby supporting continuous employee competency development. In addition, technological integration assists organizations in competency mapping, skill gap analysis, and objective performance evaluation. Despite challenges in implementation, the integration of technology in human resource development represents a strategic approach to improving organizational competitiveness in a dynamic and rapidly changing work environment.